Microfacies and depositional model of the Lower Mahil Formation (outcrop Khuff-equivalent (KS-1)) in Jabal Akhdar, Northern Oman: Implications for reservoir characterization. (March 2023) - Al Raqaishi, Rasha Ali; Moustafa, Mohamed S.h.; El-Ghali, Mohamed A.K.; Abbasi, Iftikhar Ahmed; Al-Awah, Hezam; Al Sarmi, Musaab Shakir; Al-Sayigh, Abdulrazak; Al-Shukaili, Marwa
Abstract: This study presents a detailed microfacies analysis of the Lower Triassic Mahil Formation (Khuff outcrop equivalent (KS-1)) in Jabal Akhdar, at the Saiq Plateau and Wadi Sahtan areas of Northern Oman.Two sections were measured and sedimentologically logged along a depositional dip profile emphasizing color, lithology, grain components, bed thickness, the nature of bed contact, lateral continuity of beds, and fossil content.One hundred and eighty fresh rock samples were collected from various lithofacies.The collected samples were thin-sectioned after blue epoxy was impregnated, and then they were half stained with Alizarin Red S and Potassium Ferricyanide for mineralogical identification.The point-counted compositions were determined by counting 300 points for each thin section to reconstruct the original components, obtain precise quantification, develop representative microfacies, and construct the depositional model for the Lower Mahil Formation.Accordingly, eighteen microfacies types representing different carbonate ramp environments were identified; two are only recognized in the Wadi Sahtan logged section, ten are restricted to the Saiq Plateau logged section, and six are common for both sections.The Lower Mahil Formation consists of backshoal (inner ramp) to foreshoal (mid-ramp) carbonate facies, with shoal (ramp crest) facies restricted to the Saiq Plateau logged section.The backshoal facies was characterized by abundant non-skeletal grains with breccia.The shoals were predominantly oolitic and intraclastic packstone-grainstone.Foreshoal carbonate facies, on the other hand, has mixed skeletal and non-skeletal grains with weakly developed hummocky cross-stratified beds.The shallow-water foraminiferal and oolitic packstone/grainstone facies are the potential reservoir intervals, whereas the wackestone facies is the non-reservoir intervals within the Lower Mahil Formation.The detailed sedimentological and microfacies analysis helped characterize the Lower Mahil Formation for better recognizing the potential reservoir vs.no-reservoir.This study can be a key reference to correlate the Lower Mahil Formation locally and regionally. Highlights: The studied Formation is one of the most prolific reservoirs in the Middle East, and this study reveals the potential reservoir in two sections. The main finding is that the eighteen different microfacies types were distributed randomly in three different environments. The analysis procedure employed shown that the Saiq Plateau section is shallower than the Wadi Sahtan section.